Crosstalk between angiogenesis and immunosuppression mediated by dysfunctional CD8 T cells - Bannoud, Nadia (2019)
Aberrant angiogenesis and immune evasion stand out as hallmarks of cancer since they are essential processes for the development of most solid tumors. T cell exhaustion is one of the mechanisms that accounts for immune escape in the tumor microenvironment restraining effective antitumor response. The aim of this study was to investigate the crosstalk between angiogenesis and immunosuppression, focusing on exhausted CD8 T cells. To address this, we purified splenic CD8 T cells from C57/BL6 mice and exposed them to an activation/reactivation cycle using anti CD3/CD28, under normoxic or hypoxic conditions, and characterized them as activated or exhausted (ex) T cells according to expression of inhibitory receptors and cytokines. CD8ex showed higher expression of PD-1 and Tim-3 and lower levels of IL-2, TNF, IFN-γ and grzB (p<0.05). Moreover, degranulation of CD8ex was impaired as shown by low levels of CD107a expression (p<0.05). Interestingly, hypoxia and VEGF augmented the dysfunctional phenotype of CD8 T cells (p<0.05), reinforcing the idea that vascular and immune compartments are closely interconnected. To evaluate the impact of CD8ex on vascularization, we carried out an angiogenesis array, and in vitro angiogenesis assays using conditioned media derived from these cells. We found that CD8 T cells secrete proangiogenic factors, that are modulated during the activation process towards a proangiogenic profile. Importantly, CD8ex showed higher pro-angiogenic capacity, as shown by their ability to induce endothelial cell tubulogenesis and migration. Of note, hypoxia significantly enhanced the pro-angiogenic capacity of CD8ex (p<0.05). Taken together our results suggest a crosstalk between angiogenesis and immunosuppression, executed by CD8 T cells. Our results may contribute to generate a more integrated picture of the tumor microenvironment with critical implications in clinical settings involving combination of immunotherapeutic and anti-angiogenic modalities.